Smart contract and blockchain: disruptive or constructive to Islamic financial services in Malaysia - Mohd. Zain, Nor Razinah; Aulia, Mahdiah (2019)
Reaching towards 2020, there is an apparent increased in the reliance of smart contract and blockchain in banking and finance sector. While the tendencies of investors towards the smart contract and blockchain are positive in nature, the trends in the banking and finance sector are varied according to jurisdictions. Leading towards having a more innovative banking and finance system, the Islamic financial services institutions in Malaysia are making a serious consideration towards smart contracts and blockchain. By adopting a qualitative research methodology and the collected data from the field, this research views the latest trend in Islamic financial services institutions towards smart contract and blockchain. This research stands to achieve two main objectives. Firstly, to evaluate the general trend of Islamic financial institutions towards smart contract and blockchain in Malaysia. Secondly, to examine the current challenges that the Islamic financial services industry needs to overcome in adopting a workable smart contract and blockchain system. Based on the findings, despite of challenges, Islamic financial services institutions in Malaysia may adopt smart contract and blockchain. Instead of taking such technologies as disruptive, smart contract and blockchain are constructive to boost the Islamic financial services industry in Malaysia.